Monkeypox: epidemiological situation, diagnostics, prevention, new challenges and problems of our time - Belyakova E.N.; Shipulin G.A. (Клиническая микробиология и антимикробная химиотерапия)
Monkeypox (mpox) is a particularly dangerous zoonotic infectious disease, the causative agent of which belongs to the numerous family Poxviridae, subfamily Chordopoxvirinae, genus Orthopoxvirus and belongs to the I pathogenicity group; genetically close to the smallpox virus [1]. Until recently, most cases of infection with orthopoxviruses were sporadic, did not lead to epidemic outbreaks and were difficult to register [2]. At the same time, it is believed that the formed immunity to smallpox is capable of protecting against infection with mpox at a level of 85% [3]. However, in the last decade, there has been a visible increase in the incidence of monkeypox [4], which cannot but cause concern. Over the past 50 years in Africa, sporadic incidence has increased from isolated cases to several thousand per year. At the same time, the number of cases of monkeypox virus (MPXV) transmission to humans is increasing, and imported cases of monkeypox are increasingly occurring, with the virus spreading beyond natural foci in Africa [5]. For example, in 2023, a new mpox outbreak began in the Democratic Republic of the Congo (DRC), with subsequent cases reported in Burundi, Kenya, Rwanda, and Uganda, and on 14 August 2024, the head of the World Health Organization (WHO), Tedros Adhanom Ghebreyesus, declared the ongoing mpox outbreak a public health emergency of international concern under the International Health Regulations (2005), noting that a coordinated international response is needed to stop the spread of the disease. The situation in the DRC associated with MPXV clade I continues to evolve, with the number of cases steadily increasing since late 2022. The new outbreak is associated with new MPXV clade Ib strains that are spreading in the eastern provinces of the DRC and in countries bordering the DRC [6, 7]. This review aims to describe the current epidemiological situation, modern diagnostic capabilities and specific prevention of mpox. The review used publications presented in the main international medical information databases PubMed, Web of Science, Embase, Elibrary, as well as data from WHO, Centers for Disease Control and Prevention (CDC USA, ECDC, Africa CDC), NCBI GenBank and GISAID. An epidemiological method was used to analyze the publications.